Radiation treatment for adult rare cancers: Oldest and newest indication. (March 2021) - Fiorentino, Alba; Gregucci, Fabiana; Desideri, Isacco; Fiore, Michele; Marino, Lorenza; Errico, Angelo; Di Rito, Alessia; Borghetti, Paolo; Franco, Pierfrancesco; Greto, Daniela; Donato, Vittorio
Abstract: Aim: Aim of this analysis is to review the role of RT in the management of several rare tumors for adult patients. Methods: Collection data regarding RT and rare tumors was made by Pubmed. Results: For mucosal melanomas, RT is prescribed, being associated with lower local recurrence rate. For trachea tumors, RT was used as adjuvant or salvage treatment for unresectable disease. For pNET, RT can be a suitable option for post-surgical or unresectable/borderline. For bronchopulmonary neuroendocrine tumors the role of adjuvant treatments is uncertain. For hepatobiliary and ovarian malignancy, stereotactic body RT (SBRT) is a promising approach. For soft tissue sarcoma, perioperative treatments are indicated, and a growing role of SBRT in oligometastatic disease is recognized. For endocrine tumors, adjuvant RT has demonstrated benefits through reducing recurrence risk. Conclusion: The radiotherapy is a frequent indication in adult rare cancers; thus the role of Radiation Oncologist must not be neglected.